A fault-tolerant topology for single-phase H-bridge inverters addressing open- and short-circuit failures for industrial applications - Chouaib Djaghloul; Noman Khan; Khalil El Khamlichi Drissi; Kambiz Tehrani (Franklin Open, 2025)
This paper proposes a fault-tolerant topology for single-phase inverters, designed to sustain functionality following open- or short-circuit failures in one of its semiconductor switches. A simple approach is employed for the fault detection mechanism, using the load current, the switch current, and the switch gate voltage. Once a fault is detected and isolated, a redundant leg comprising two semi-conductors is connected to replace the faulty one after it has been eliminated using isolation relays. The effectiveness of this approach is validated through simulation using MATLAB Simulink, demonstrating both the speed and efficacy of the fault-tolerant topology in restoring normal operation post-fault occurrence.